(untitled) (American Journal of Islam and Society, 1998)
Infertility is normally thought to be a problem for the rich, Western world, overpopulation the problem of the poor, Third World. But is this dichotomy built on empirical facts or on racial prejudices? Available statistics surprisingly reveal an infertility belt from the Sudan and across Africa, where the problem in certain countries is extremely widespread. This and the AIDS epidemic threaten, according to Marcia lnhom, to depopulate large areas. In Egypt, official statistics show the infertility rate lo be 8%, a number Inborn regards as unrealistically low, but still it is eight times the number in Korea and Thailand. Despite such high figures, the focus in Egypt is only on hypofertility and family planning. Even so, the population is stilJ increasing due, says lnhom, to politicians’ and health personnels’ ignorance of the dialectic between fertility and infertility. lnhom goes a long way toward exposing the "overpopulation problem" as a myth. She takes as her starting point the U.N. declaration of human rights, which asserts the right of all individuals to found a family, and transfers the focus to childless Egyptians, which she claims is a muted group. Quest for Conception is the first comprehensive account of infertility in the Third World and represents a breakthrough in medical anthropology. Because this topic is highly gendered, the book also makes an important contribution to gender studies. Her 100 childless informants from Alexandria are all poor Muslim women, and Quest for Conception can be read both as a study of poverty and of female Islamic practice. lnhom analyzes the extent of infertility, its causes and existing forms of treatment (both ethno- and biomedical), and potential reforms. Her material is based on childless women’s medical life stories-which often contain an astonishing variety of treatments. In addition, she has followed them through 15 months of desperate search for children (1988-89). In all this time, only one(!) succeeded in giving birth. The others presumably are continuing their restless search for the child they need in order to realize their one and only career-motherhood. The women’s own experiences and emotional reactions, their subjective understanding of causes and different methods of treatment, and their strategies are central to lnhom’s very humane ethnography. But this micromaterial is continuously ...